Pola Hermenetik Sastra Hikmat Orang Ibrani - Sonny Eli Zaluchu (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat)
Sonny Eli Zaluchu, The Hermenetic Pattern of Hebrew Wisdom Literature. Hebrew Wisdom Literature is one of the most distinctive kinds of literature that can found in the Old Testament. Particular hermeneutic patterns are needed to interpret literary books. The writings of the wisdom literature of the Hebrew people are rich in various types of literary styles from being oral traditions to written forms and being part of the Old Testament canon. This paper aims to form a hermeneutic pattern in the form of defining literary categories, capturing the main ideas of the writer, seeing the text in context, and paying attention to the style of language. Studying these four patterns will help the interpreter elevate the meaning of the contents of the literature of Wisdom. Writing presented in a descriptive, analytical form.